Effects of rhizosphere oxygen concentration on root physiological characteristics and anatomical structure at the tillering stage of rice. (7th April 2020) - Xu, Chunmei; Chen, Liping; Chen, Song; Chu, Guang; Wang, Danying; Zhang, Xiufu
Abstract: Oxygen is essential for all aerobic organisms. Higher plants need oxygen to sustain metabolism and growth. After experiencing anaerobic stress for a period of time, most plant tissues will be damaged. This study examined the physiological characteristics and anatomical structures in the root tips of rice seedlings (cultivars Xiushui09 and Chunyou84) in response to different rhizosphere oxygen environments. The results showed that moderate oxygen (MO: 2.5–3.5 mg L −1 ) increased the dry weight accumulation and formation of rice roots (including length, surface area, number of tips) in both genotypes. Compared to under normal conditions (NC), the magnitudes of increase in these four variables were 4.67, 66.40, 35.44 and 49.50% in Xiushui09 and 12.25, 15.59, 13.57 and 13.48% in Chunyou84, respectively. Low oxygen (LO: 0–1.0 mg L −1 ) stress decreased the root surface area but increased root volume and average diameter. LO and high oxygen (HO: >6.8 ± 0.21 mg L −1 ) stress each damaged the apical cells' ultrastructure, reduced the number of organelles, and increased electrical conductivity. Meanwhile, the root activity and respiration of rice seedlings decreased; the abscisic acid content increased compared to levels under NC. Under MO treatment, the cell membrane was not damaged, the root tip organelles were rich, the soluble protein content, root activity, respiration rate and gibberellic acid content increased compared to levels under NC; the magnitudes of these increases were 24.76, 36.00, 8.00 and 283.00% in Xiushui09 and 4.78, 40.00, 15.45 and 49.35% in Chunyou84, respectively. In conclusion, MO optimised rice root morphology and enhanced root physiological activity. Abstract : Rice seedling morphological distribution was optimal under MO (2.5–3.5 mg L −1 ) treatment. The physiological activity of the rice root is closely related to the ultrastructure of the root tip. Under MO treatment, the apical cell structure was intact, the number of organelles increased, the apical cell contents were abundant and the root physiological activity was strong.